Development of Islamic Education Teaching and Learning Methods Throughout History - Abdillah; Muhtadi Abdul Mun’im (Penerbit Hellow Pustaka, 2025)
Teaching and learning methods in the context of Islamic education have experienced a significant transformation from the early times to the modern era. This article explores the evolution of these methods, from traditional approaches focused on memorization to modern methods that utilize digital technology. This research applies a historical approach to analyze changes and adjustments in teaching methods that have been made over time. Apart from that, this research also examines the various challenges faced by Islamic educators in trying to maintain a balance between traditional and modern values ​​in the teaching process. In this study, it is shown how educators attempt to integrate modern aspects into Islamic education, without ignoring the basic principles that have existed for a long time. This diverse approach not only enriches the learning experience, but also creates space for students to understand and apply Islamic values ​​in a broader context. With digital technology, for example, learning methods have become more interactive and interesting, allowing students to be actively involved in the educational process. The results of this research indicate that transformation in Islamic education teaching methods has the potential to improve the quality of the curriculum and effectiveness in the teaching and learning process. By utilizing the latest innovations, educators can overcome various challenges that arise, and provide a more relevant and meaningful educational experience for the younger generation. Therefore, it is important for educators to continue to adapt and develop teaching methods that suit the needs of the times, while still maintaining the core values ​​of Islamic education.